Implementasi Pengendalian Proses Avsec Awareness dan Background Check dalam Penerbitan Pas Orang Tetap di Otoritas Bandar Udara Wilayah III - Arif Rakhman Maulana; Amelia Puspa Tamara (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
An Airport Pass is a special permit granted to an individual or group to enter a restricted area of an airport environment. The airport area has areas that can only be passed by officers and aviation service users with certain requirements such as, Security Restricted Area, Sterile Area, Restricted Area, Public Area. Avsec Awareness is the provision of counseling and understanding of aviation security concerns, and Background Check is a background check to ensure that applicants are not involved in crimes, falsifying documents, providing false information/data and being involved in prohibited organizations. The role of the Airport Authority Office in controlling the issuance of Airport Passes is very important to ensure that individuals who have access to restricted areas are in accordance with applicable regulations. This study aims to determine the implementation of avsec awareness & background check process control in the issuance of permanent person passes and identify the obstacles faced during the implementation of the process. The method used in this study is a qualitative method, with data obtained from primary and secondary sources. Primary data was collected through observation and interviews, while secondary data was sourced from Standard Operating Procedures (SOPs), photo documentation, and literature studies. The data analysis techniques used include data reduction, data presentation, and conclusion drawn, by testing the validity of the data using triangulation techniques. The results of this study show that the Region III Airport Authority Office can carry out its duties in accordance with SOPs, including control of the avsec awareness and background check process in the issuance of permanent person passes and the responsibility of the Region III Airport Authority Office in conducting supervision for airport pass holders.